A note on the energy moments - Pimentel, B. M.; Zimerman, A. H. (IOP Publishing, 1980)
The relationship between the Buslaev-Faddeev and Percival methods for studying the moments Tr(Hp) is shown explicitly by analytic continuation of the generalised zeta function written in terms of the partition function.